DAMPAK IMPLEMENTASI PERUBAHAN DASAR PENGENAAN PAJAK BERDASARKAN UNDANG-UNDANG HARMONISASI PERATURAN PERPAJAKAN TERHADAP PAJAK PENGHASILAN TERUTANG WAJIB PAJAK ORANG PRIBADI KARYAWAN (STUDI KASUS PADA PT. BERKAT SEJATI) - Farida Aryani (Jurnal Ilmiah Akuntansi Rahmaniyah, 2023)
This research is a descriptive research with analytical techniques using comparison of results of calculating tax payable WPOP at PT. Berkat Sejati. This study aims to determine the impact of implementing changes to the tax base based on HPP Law on tax payable by WPOP employees of PT. Berkat Sejati. Data analyzed is secondary data in the form of amount of tax owed by WPOP deducted by the company in 2022. The results of this study indicate that the implementation of changes to the tax base based on the Law on Harmonization of Tax Regulations at PT. Berkat Sejati has impact of reducing income tax payable for WPOP employees by Rp 22,545,826. Generally, the application of 5% rate charged for PKP is Rp 60,000,000, will increase income tax payable by Rp 500,000. Meanwhile, application of 15% rate imposed on PKP is maximum of Rp 200,000,000, will have effect of reducing income tax payable by Rp 1,500,000. Thus, when WPOP obtains PKP above Rp. 60,000,000 up to no more than Rp 250,000,000, there will be decrease or savings in income tax of Rp 1,000,000.